(untitled) (Research Nepal Journal of Development Studies, 2020)
Women empowerment is a process and contextual in situations. There are two approach of women empowerment. Agency approach focuses only on agency and structure approach on structure; however, both approach are incomplete. My argument is agency and structure both approach is inseparable. Structure and agency come together in structuration. This article is based on the Brahma Kumaris World spiritual university (BKWSU) as structure and Brahama Kumaris (BK, Daughter of Barhma) as agency in women empowerment process. BKWSU is a women led largest organization in the world. The objective of the study is to explore the process of empowerment and contribution of spiritual organization in the area of women empowerment. The qualitative descriptive approach with intensive literature review method the study has been conducted in Rajyog centers of Kathmandu. In conclusion, BKs have strong belief that self-confidence is the most powerful means of empowerment. They do not have the sense of male or female but they think that they all are soul. It ca be taken as spiritual empowerment or inner empowerment which is prerequisite for further empowerment.